Ultrasonic Features of Uncommon Congenital Heterotopic Colon and Pancreas in the Neck: An Extremely Rare Case Report - Wei, Yingli; Pan, Zhihao; Kang, Xiaoling; Huang, Cuiqing; Chen, Dan (Frontiers in Pediatrics, 2021)
Congenital heterotopic colon and pancreas localized to the neck has not been reported. Herein, we describe an extremely uncommon case of congenital heterotopic colon and pancreas aberrantly presented within a cyst on the neck, and the thickened wall of the cyst on ultrasound may represent an important ultrasonic feature.